A Five-Dimensional Model of Creativity and its Assessment in Schools. Issue 4 (1st October 2016) - Lucas, Bill
ABSTRACT: Creativity is increasingly valued as an important outcome of schooling, frequently as part of so-called "21st century skills." This article offers a model of creativity based on five Creative Habits of Mind (CHoM) and trialed with teachers in England by the Centre for Real-World Learning (CRL) at the University of Winchester. It explores the defining and tracking of creativity's development in school students from a perspective of formative assessment. Two benefits are identified: (a) When teachers understand creativity they are, consequently, more effective in cultivating it in learners; (b) When students have a better understanding of what creativity is, they are better able to develop and to track the development of their own CHoM. Consequently, the Organisation for Economic Co-operation and Development has initiated a multicountry study stimulated by CRL's approach. In Australia work to apply CRL's thinking on the educational assessment of creative and critical thinking is underway.